2018
DOI: 10.1111/tpj.14161
|View full text |Cite
|
Sign up to set email alerts
|

A coupled role for CsMYB75 and CsGSTF1 in anthocyanin hyperaccumulation in purple tea

Abstract: Cultivars of purple tea (Camellia sinensis) that accumulate anthocyanins in place of catechins are currently attracting global interest in their use as functional health beverages. RNA-seq of normal (LJ43) and purple Zijuan (ZJ) cultivars identified the transcription factor CsMYB75 and phi (F) class glutathione transferase CsGSTF1 as being associated with anthocyanin hyperaccumulation. Both genes mapped as a quantitative trait locus (QTL) to the purple bud leaf color (BLC) trait in F 1 populations, with CsMYB7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 56 publications
9
86
0
Order By: Relevance
“…Earlier work in litchi revealed that the expression of LcGST4 was also activated by LcMYB1 (Hu et al, 2016). Similar results were also reported in strawberry, apple, tea and kiwifruit (Jiang et al, 2019;Liu et al, 2019;Luo et al, 2018;Wei et al, 2019). Data from the dual-luciferase assays performed in this study suggested that the transcriptional activity of the PpGST1 promoter is directly up-regulated by PpMYB10.1 rather than PpMYB10.2 and PpMYB10.3, and it was further activated by PpbHLH3 through the interaction between PpMYB10.1 and PpbHLH3.…”
Section: Expression Of Gst Is Regulated Via Different Meanssupporting
confidence: 88%
See 1 more Smart Citation
“…Earlier work in litchi revealed that the expression of LcGST4 was also activated by LcMYB1 (Hu et al, 2016). Similar results were also reported in strawberry, apple, tea and kiwifruit (Jiang et al, 2019;Liu et al, 2019;Luo et al, 2018;Wei et al, 2019). Data from the dual-luciferase assays performed in this study suggested that the transcriptional activity of the PpGST1 promoter is directly up-regulated by PpMYB10.1 rather than PpMYB10.2 and PpMYB10.3, and it was further activated by PpbHLH3 through the interaction between PpMYB10.1 and PpbHLH3.…”
Section: Expression Of Gst Is Regulated Via Different Meanssupporting
confidence: 88%
“…Heterologous overexpression of VviGST4 ( Vitis vinifera ) and AcGST1 ( Actinidia chinensis ) in Arabidopsis tt19 mutant can functionally complement both the anthocyanin‐less phenotype in plant and the PA‐deficient phenotype in seed coat (Liu et al , ; Pérez‐Díaz et al , ). However, in this study, PpGST1 only possessed the capacity to functionally complement the anthocyanin‐less phenotype of Arabidopsis tt19 mutant but not the PA‐deficient phenotype in the seed coat, which was similar to the result of An9 ( Petunia hybrida ), LcGST4 ( Litchi chinensis ), RAP ( Fragaria ananassa ), CsGSTF1 ( Camellia sinensis ) and MdGSTF6 ( Malus domestica ) in the tt19 complementation assay (Hu et al , ; Jiang et al , ; Kitamura et al , ; Luo et al , ; Wei et al , ). These data indicated that PpGST1 plays a pivotal role in anthocyanin transport and differed from AtTT19 , VviGST4 and AcGST1 which also participate in seed deposition of PAs.…”
Section: Discussionsupporting
confidence: 73%
“…Plant GSTs are encoded by a large gene family, and are soluble and abundant in the cytosol [26,50,51]. They can be divided into eight subgroups, among which the tau and phi classes play key roles in flavonoid transport [52]. Bronze 2 (bz2) in maize was the first tau class GST reported to be involved in anthocyanin accumulation; bz2 produces yellow skin kernels because of disabled anthocyanin transport into the vacuole [53].…”
Section: Discussionmentioning
confidence: 99%
“…Bronze 2 (bz2) in maize was the first tau class GST reported to be involved in anthocyanin accumulation; bz2 produces yellow skin kernels because of disabled anthocyanin transport into the vacuole [53]. Anthocyanin deposition is also affected by genes in the phi class, such as AtGSTF12 in Arabidopsis [54,55], FvRAP in strawberry [26], CsGSTF1 in tea [52], and VvGST4 in grapevine [56]. Interestingly, these phi-class GSTs show extensive functional diversification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation